Effectiveness of Edpuzzle-Based Learning Videos in Oriental Food Preparation - Amanda, Nafisa Yustika; Sutopo, Yeri; Saptariana, Saptariana (Universitas Negeri Semarang, 2025)
The low achievement of practical learning in food preparation, particularly in the topic of oriental food management, has been a concern. Previously, oriental food preparation was taught through live demonstrations, as there were no learning videos aligned with the learning achievement standards (CP) and learning objectives (ATP). Additionally, students who were positioned at the back of the class often had difficulty clearly observing the teacher's demonstration. Thus, there is a need for a solution in the form of developing an interactive learning video media based on the Edpuzzle application. This study aims to test the effectiveness of Edpuzzle-based learning videos on psychomotor skills in preparing oriental food. The research method used a quantitative approach with a two-group pretest-posttest design. The instruments used included pre- and post-test assessments as well as an evaluation sheet. Data were analyzed using normality tests, homogeneity tests, T-tests, n-gain tests, and user feedback questionnaires. The results showed that the use of video led to a significant improvement in students' skills, with a moderate effectiveness category based on the N-gain test results. Additionally, user feedback indicated that the video was practical and suitable for use in learning. Based on these results, it can be concluded that the developed learning video is effective as a media tool for teaching oriental food preparation, as evidenced by the improvement in pretest and posttest scores, categorized as moderate. This research is beneficial as a learning medium for culinary students, particularly in the area of oriental food preparation, and can enhance student learning outcomes.